A highly zinc-selective ratiometric fluorescent probe based on AIE luminogen functionalized coordination polymer nanoparticles. Issue 35 (20th April 2017) - Lin, Na; Zhang, Qin; Xia, Xin; Liang, Mengyu; Zhang, Shihong; Zheng, Liyan; Cao, Qiue; Ding, Zhongtao
Abstract : A highly zinc-selective ratiometric fluorescent probe was developed based on the cation exchange process of Tb-HDBB-CPNs with Zn 2+ . Abstract : Coordination polymer nanoparticles (CPNs) formed by self-assembly of metal ions (or clusters) and organic bridging ligands through coordination bonds provide a unique platform for designing multifunctional nanoparticles. In this work, we report a ratiometric fluorescent probe for Zn 2+ based on CPNs, which were prepared from AIE fluorophore HDBB molecules with metal ions. The CPNs are composed of HDBB molecules with Tb 3+ (named Tb-HDBB-CPNs) which displayed a matrix coordination-induced emission peak at a wavelength of 590 nm, while CPNs formed by HDBB molecules and Zn 2+ (named Zn-HDBB-CPNs) showed a distinctive fluorescent property with a blue emission peak wavelength of 470 nm. Based on the cation exchange process of Tb-HDBB-CPNs with Zn 2+, a highly selective ratiometric fluorescent probe for the determination of Zn 2+ in aqueous solution was developed with a linear range from 0.1 to 60 μM and a detection limit of 50 nM. Our approach using AIE molecules as organic ligands for the construction of CPNs paves a way toward AIE functionalized materials with ratiometric fluorescence response and will find wide applications in chemical sensing.